2019
DOI: 10.1039/c9nj00462a
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional ZSM-5/hydrotalcite composite for enhanced production of 5-hydroxymethylfurfural from glucose

Abstract: Over 65% yield of 5-hydroxymethylfurfural from glucose was obtained under mild condition by using ZSM-5/HT composite as acid/base bifunctional catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…10 Besides, HMF can be used to synthesize 2,5-furandicarboxylic acid, a promising monomer for the manufacture of bio-based polyethylene furanoate (with better mechanical strength and oxygen/CO2 barrier properties) to replace the petroleum-based polyethylene terephthalate. 11 In the past decades, numerous research efforts have been devoted to converting bio-based carbohydrates into HMF in various catalytic reaction systems, such as the use of catalysts (including among others mineral acid, 12,13 metal salts 14 and solid acid catalysts like HfO(PO4)2, 15 activated carbon, 16 zeolite, 17 TiO2, 18 Ta-W oxide 19 and novel mesoporous carbon 20 ), and the use of water or other organic solvents, 21,22 aqueous-organic biphasic solvent system 18,23,24 as well as sub-or supercritical systems. 25,26 Fructose, derived from the hydrolysis of biomass (rich in the cellulosic component), 27,28 is considered as a preferred starting feedstock for HMF synthesis since the furanic structures thereof make it easier to be converted with a higher selectivity towards HMF as compared to raw biomass.…”
Section: Introductionmentioning
confidence: 99%
“…10 Besides, HMF can be used to synthesize 2,5-furandicarboxylic acid, a promising monomer for the manufacture of bio-based polyethylene furanoate (with better mechanical strength and oxygen/CO2 barrier properties) to replace the petroleum-based polyethylene terephthalate. 11 In the past decades, numerous research efforts have been devoted to converting bio-based carbohydrates into HMF in various catalytic reaction systems, such as the use of catalysts (including among others mineral acid, 12,13 metal salts 14 and solid acid catalysts like HfO(PO4)2, 15 activated carbon, 16 zeolite, 17 TiO2, 18 Ta-W oxide 19 and novel mesoporous carbon 20 ), and the use of water or other organic solvents, 21,22 aqueous-organic biphasic solvent system 18,23,24 as well as sub-or supercritical systems. 25,26 Fructose, derived from the hydrolysis of biomass (rich in the cellulosic component), 27,28 is considered as a preferred starting feedstock for HMF synthesis since the furanic structures thereof make it easier to be converted with a higher selectivity towards HMF as compared to raw biomass.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the amount of catalyst with the mass ratio of catalyst and carbohydrate used in the conversion of carbohydrates played a vital role in maximizing the yield of HMF. 99 Subsadsana et al 99 studied the catalytic activity of ZSM-5/hydrotalcite composite F I G U R E 1 6 200 nm SEM high magnification of 10%TiO 2 C_S catalyst 41 catalyst on HMF synthesis from glucose and found that the highest conversion of glucose achieved at catalyst to glucose mass ratio of 0.1:1; however, as the number of catalysts increased, the yield of HMF decreased due to decline in the selectivity of HMF and enhanced byproducts formation. Xie Y et al 114 stated that the increased yield of HMF was enhanced by the presence of more acid sites on the catalyst surface, as the catalyst loading of Zr(IV)-salen-MCM-41 catalyst increased from 30 to 50 mg, but when the catalyst loading more than 60 mg, HMF yield slightly decreased due to excessive catalyst promoted the undesired byproducts formation.…”
Section: Effects Of Catalyst Loading and Substrate Concentration On T...mentioning
confidence: 99%
“…Recyclability of the catalyst's reusability is an important parameter to evaluate the economic cost and efficiency of the catalyst used in carbohydrates-to-HMF dehydration for green and sustainable industrial-scale production. 13,23,74,99 Wang et al 105 examined the stability and reusability of the SBA-15-SO 3 H catalyst, in which the catalyst achieved a consistently high activity of fructose-to-HMF conversion for five cycles. This situation indicated that the catalyst has high stability and reusability due to the concentration of acid sites on the catalyst remain the same after several cycles.…”
Section: Catalyst Recyclabilitymentioning
confidence: 99%
See 2 more Smart Citations